The effect of geometric structure on stiffness and damping factor of wood applicable to machine tool structure - Susilo Adi Widyanto; Achmad Widodo; Sri Nugroho; David Siahaan (Chemical Engineering Diponegoro University, 2013)
Stiffness and vibration damping capability are important criteria in design of machine tool structure. In other sides, the weight of machine tool structure must be reduced to increase the handling capability. This paper presents an analysis of the effect of geometric structure on stiffness and vibration damping of wood structure. The stiffness was analysed using numerical method, so called finite element method (FEM), while the vibration damping capability was experimentally tested. Vibration testing was also performed to wood structures with sand powder filled into its rectangular hole to observe the its effect on damping factor. Simulation results show that the cross ribs structure yielded minimum mass reduction ratio compared to the three square holes as well as the single rectangular hole structures. While the vibration test results explained that the damping factor of Shorea laevis wood was higher than that Hevea braziiensis wood. The use of sand powder as vibrating mass in closed-box structure effectively increased the damping capability, for single rectangular hole structure the damping factor was increased from 0.048 to 0.079doi: http://dx.doi.org/10.12777/ijse.4.2.2013.57-60[How to cite the article: Widyanto, S. A., Widodo, A., Nugroho, S., & Siahaan, D. (2013). The effect of geometric structure on stiffness and damping factor of wood applicable to machine tool structure. INTERNATIONAL JOURNAL OF SCIENCE AND ENGINEERING, 4(2), 57-60. doi: http://dx.doi.org/10.12777/ijse.4.2.2013.57-60]